Linking the micro- and macro-level dimensions of lifestyle-routine activity and opportunity models of predatory victimization - Sampson, Robert J. (Journal of quantitative criminology, 1987)
This paper explores the importance of linking the micro- and macro-level dimensions of household and personal victimization. Specifically, we use the British Crime Survey, a nationally representative sample of 10,905 residents of England and Wales, to examine differences in victimization risk associated with demographic characteristics, lifestyle-routine activities, and community context. In general, victimization risk is highest for the young, the singles, and those who frequently go out at night or leave their homes empty. Independent of these individual-level effects, however, burglary victimization is directly related to community levels of primary (single)-individual households, family disruption, unemployment, and housing density, while personal theft is inversely related to community social cohesion (friendship networks, residential stability). Furthermore, personal theft is positively related to community “street activity” (i.e., rate at which residents go out at night on foot), regardless of individual-level lifestyle. The results thus support a multilevel opportunity model of predatory victimization.